Damage control: The modern paradigm. (July 2016) - MacGoey, Patrick; Lamb, Christopher M; Navarro, Alex P; Brooks, Adam J
It is more than 20 years since the term 'Damage control' was introduced to describe an emerging surgical strategy of abbreviated laparotomy for exsanguinating trauma patients. This strategy of temporisation and prioritisation of physiological recovery over completeness of anatomical repair was associated with improved survival in a subset of patients with combined major vascular and multiple visceral injuries. The ensuing years saw the rapid adoption of these principles as standard of care for massively injured and physiologically exhausted patients. Resuscitation of severely injured patients has changed significantly in the last decade with the emergence of a new resuscitation paradigm termed 'damage control resuscitation'. Originating in combat support hospitals, damage control resuscitation emphasises the primacy of haemorrhage control while directly targeting the 'lethal triad' of coagulopathy, acidosis, and hypothermia. Integral to damage control resuscitation is the appropriate application of damage control surgery and together they constitute the modern damage control paradigm. This review aims to discuss the modern application of damage control resuscitation and damage control surgery and to review the evidence supporting its constituent components, as well as considering deficiencies in current knowledge and areas for future research.